Whole grain foods: is sensory liking related to knowledge, attitude, or intake?. Issue 4 (11th July 2016) - Magalis, Robin M.; Giovanni, Maria; Silliman, Kathryn
Abstract : Purpose: The health benefits of whole grains are well established, yet intake remains below recommendations. Knowledge and familiarity with whole grains may increase short-term intake, but sensory properties can limit consumption. These factors usually are researched separately, thus, this study aims to explore the relationships among sensory liking, knowledge, attitudes and intake. Design/methodology/approach: This cross-sectional study had 69 college students participate in four tasks: sensory liking of whole vs refined grain bread, rice, pasta and tortillas; bitter taster status; knowledge and attitudes; and intake of whole grains. Findings: Whole wheat bread and tortillas were liked, as well as their refined grain counterparts. However, white rice and pasta were liked significantly more than the whole grain products ( p < 0.05), which are less familiar to most people. Higher consumers of whole grain foods preferred those samples to the refined product for some sensory attributes ( p < 0.05). Bitter taster status was not related to sensory preferences. Understanding and recognition of whole grains was low, but attitudes were generally positive. Whole grain intake was overestimated by the food frequency questionnaire because of problems with the instrument and also subjects' lack of understanding about these foods. Research limitations/implications: The link between preference and consumption warrants further study. The survey used to measure whole grain intake was a limitation and demonstrates the need for an accurate and efficient tool. Although knowledge about whole grains is limited, the positive attitudes expressed by participants can strategically inform outreach. If people believe that they consume more whole grains than they actually do, they may have a false sense of security. Further research with different age groups and a wider variety of foods is needed. Practical implications: Participants overestimated their consumption of whole grain foods, indicating that consumers may think that they are meeting recommended amounts but they are actually deficient in whole grain intake; thus, improved education and promotional efforts are needed. Originality/value: Few studies examine the inter-relationships among sensory preference, bitter taster status, knowledge, attitude and intake of whole grains.